Problem-Based Learning Model Assisted by Interactive Media to Improve Students Higher Order Thinking Skills (HOTS) - Taufiqurrahman Taufiqurrahman; Siti Fathonah; Farid Ahmadi; Arie Arma Arsyad; Sukmawanty Rahman (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the issue of students' low Higher Order Thinking Skills (HOTS) in Science, specifically on the topic of Acids, Bases, and Salts, in Class VII-5 at UPT SPF SMPN 40 Makassar. The research aims to evaluate how effective the Problem-Based Learning (PBL) model, supported by interactive media, is in improving students’ HOTS. It also examines the level of improvement in each learning cycle and assesses the observed HOTS development throughout the study. Additionally, the research seeks to determine whether there is a significant increase in students' HOTS after applying the PBL model with interactive media. This study follows the Classroom Action Research (CAR) methodology, conducted in two cycles that include planning, implementation, observation, and reflection. Data was collected through HOTS test results (quantitative data) and classroom observations (qualitative data). In the pre-cycle stage, none of the students passed the test, with all 30 students falling below the learning criteria. In Cycle I, 18 students passed, while 12 did not, leading to a class-wide learning completion rate of 60%, categorized as low. Classroom observations during this cycle showed a score of 59.58%, considered fair. In Cycle II, all students successfully passed, increasing the success rate to 83.33%, classified as high. Observations also improved, reaching 66.67%, categorized as good. These findings suggest that the use of Problem-Based Learning with interactive media can effectively enhance students' HOTS.